Textbook on administrative law - Leyland, Peter; Woods, Terry (New Delhi: Oxford University Press., 2002)
This text is written for anyone studying administrative law who requires a concise and readable textbook. It is specifically directed at LLB and CPE students, as well as those approaching the subject for the first time at undergraduate or postgraduate level, including non-law students in related fields
Includes index.
eng.
Keywords: Administrative law; The remedies; Tribunals and inquiries